Pengaruh Kesadaran Pajak, Pelayanan Pajak Terhadap Kepatuhan Wajib Pajak - Arslan, Rijal; Latif, Adi Sofyana; Ramdani, Chaeru Syahru; Septanta, Rananda (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
This researchis armed to knowed taxpayer service and tax officials of tax compliance. The research conducted at Kantor Pelayanan Pajak Pratama in district Temanggung on 2015. This research is casual comparative sample approach taken by insidental sampling technique with a total sample of 101 respondents. Methods pf data collection on issues related to research carried out using a questionnaires, in this form of closed questions the data taken in March 2016. The result of 101 respondents, showed that awareness of taxpayers and tax officials at the Kantor Pelayanan Pajak Pratama in district Temanggung 2015 effect on tax compliance. Calculations that have been done abtained sig value equal to vlue of alpha (0,000. Significance of test result seen probability value of 0,00 < 0,05 so the rejected. This influence he awarenesss of taxpayers and service tax officials simultaneously affect taxpayer compliance significant that the alternative hypothesis (Ha) is accepted. The result showed no significant relationship between awareness of taxpayers and service ta officials on tax compliance.